Refinement and standardization of storage procedures for clonal crops. Global Public Goods Phase 2. Part 2: Status of in vitro conservation technologies for: Andean root and tuber crops, cassava, Musa, potato, sweetpotato and yam - Benson, E.E.; Harding, K.; Debouck, Daniel G.; Dumet, D.; Escobar, R.; Mafla, G.; Panis, Bartholomeus; Panta, A.; Tay, D.; Houwe, Ines van den; Roux, N. (CGIAR System-wide Genetic Resources Programme, 2011)
Among the collective actions of the World Bank-funded Global Public Goods Phase II Project (GPG2), the following collaborative activity: “Refinement and standardization of storage procedures for clonal crops” was given to the CGIAR’s In Vitro Genebanks, represented by the Clonal Crop Task Force (CCTF) composed of genetic resources research staff from the four centres: Bioversity International, CIAT, CIP and IITA. These hold the in trust collections of Musa, cassava, potato, sweetpotato, yam and Andean root and tuber crops (ARTCs). The overarching aims of this activity were to: (1) review the status of vitro conservation in the context of the GPG2 project with an emphasis on the mandated clonal crops; (2) survey the facilities, storage protocols and practices of CGIAR’s clonal crop genebanks; (3) collate and review this information with a view to developing quality and risk management systems to support the production and validation of multi-crop best practice guidelines. Outputs from this activity are designated as a three part ‘trilogy’: Part II, “Status of in vitro conservation technologies for Andean root and tuber crops, cassava, Musa, potato, sweetpotato and yam” provides a status update on the mandate clonal crops. As tasked by GPG2, it includes lessons learnt, critical point analyses and the priority research needs of CGIAR’s in vitro genebanks.